Kemampuan Berpikir Kreatif dalam Memecahkan Masalah Teorema Pythagoras Ditinjau dari Gaya Belajar Siswa Kelas VIII SMPN 1 Taliwang Tahun Pelajaran 2021/2022 - Zulfa Wahusna; Sripatmi; Junaidi; Nani Kurniati (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe students' creative thinking skills in solving problems Pythagorean Theorem in terms of the learning style of class VIII students of SMPN 1 Taliwang, with the type of the research used is descriptive research. The research instrument used is a questionnaire, creative thinking skills test and interviews. The sampling that used in this study is purposive sampling technique so that the samples were students of class VIII-5 and VIII-7 SMPN 1 Taliwang in the academic year 2021/2022 which consists of 59 students who were then given learning style questionnaire obtained two students with visual learning styles, two students with auditory learning styles and two students with kinesthetic learning styles who were then given a creative thinking ability test and Interview. The results showed that subjects with visual learning styles had the ability to creative thinking which is in the category of creative enough, by meeting the indicators of fluency and flexibility with percentage respectively 100% and 50% but have not been able to meet the indicators of novelty with percentage 8%. Subjects with auditory learning style have the ability to think creative who are in the category of quite creative, by meeting the indicators of fleksibility dan fluency with percentage respectively 75% and 79% but have not been able to meet the indicators of novelty with percentage 4%. Subjects with kinesthetic learning styles have the ability to think creatively in the less creative category, by meeting the fluency indicator with a percentage of 100%, and not yet able to meet the flexibility indicator with a percentage of 0%, and the novelty indicator with percentage of 12.5%.